Representation of Power in Leila S. Chudori’s Novel Laut Bercerita: A Semiological Approcah by Roland Barthes - Muhammad Dzulfikar Putra Effendi; Fafi Inayatillah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This research is motivated by the fact that Leila S. Chudori’s novel Laut Bercerita represents the history of the repressive power of the New Order through complex symbolic signs, requiring semiological theory to reveal the ideological meaning behind the text. This study aims to describe: (1) the denotative meaning of power, (2) the connotative meaning of power, (3) the mythical meaning of power, and (4) the representation of power in the novel. The method used is descriptive-qualitative with Roland Barthes’ semiological approach. The primary data source is the text of the novel Laut Bercerita. Data collection was done through close reading, while data analysis followed Barthes’ three stages of signification: identification of signs, analysis of denotation and connotation, and revelation of myth, which were then synthesized into a representation of power. The results indicate that power is represented through six main forms: (1) repression and surveillance, (2) systematic violence, (3) narrative control and propaganda, (4) psychological terror, (5) structures that monopolize the state, and (6) entities leaving permanent trauma. At the myth level, the novel dismantles the New Order’s grand narrative of stability and development by showing that power is built on systematic oppression and enforced disappearances. This study concludes that power in the novel is constructed through a sign system with literal denotative meanings and ideologically laden connotative meanings, forming myths of totalitarian power and counter-myths of resistance.